Antigen-binding glycosylation inhibiting factor from a human T-cell hybridoma specific for bee venom phospholipase A2. - Gomi, H (1994)
We obtained human T-cell hybridomas that are specific for bee venom phospholipase A2 (PLA2) and constitutively secrete glycosylation inhibiting factor (GIF). Upon crosslinking of CD3, the hybridoma produced GIF having affinity for PLA2. When affinity-purified PLA2-binding GIF was used as an immunogen, monoclonal antibodies specific for the antigen-binding GIF were obtained. Monoclonal antibody 110BH3 bound the antigen-binding GIF but failed to bind the 13-kDa nonspecific GIF, as determined by both bioassay and ELISA. In contrast, 388F1, a monoclonal antibody against nonspecific GIF, gave ELISA signals with both the nonspecific GIF and the antigen-binding GIF. Gel filtration of affinity-purified antigen-binding GIF revealed the presence of a 72- to 80-kDa protein which gave ELISA signals with both 110BH3 and 388F1 and contained GIF bioactivity. Upon reduction and alkylation, the antigen-binding GIF dissociated into a 62- to 64-kDa protein which gave positive ELISA with antibody 110BH3 but no signal with antibody 388F1, and a 15-kDa protein, which gave ELISA signal with the 388F1 but not with 110BH3. Immunoblotting of a PLA2-binding GIF preparation revealed that under reducing conditions, the antigen-binding GIF dissociated a 13-kDa peptide which reacted with polyclonal antibodies against recombinant GIF. The results indicate that the 13-kDa nonspecific GIF is a subunit of antigen-binding GIF. The PLA2-binding GIF has affinity for an epitope, representing amino acid residues 19-28 in PLA2 which appears to be an external structure in the antigen.